Effect of Texture on Biodegradable Behavior of an As-Extruded Mg–3%Al–1%Zn Alloy in Phosphate Buffer Saline Medium. Issue 7 (July 2016) - Wang, Baojie; Xu, Daokui; Dong, Junhua; Ke, Wei
Abstract : In this work, the corrosion behavior of two differently oriented surfaces of an as-extruded Mg–3%Al–1%Zn (AZ31) bar in a simulated body fluid of phosphate buffer saline (PBS) medium was investigated and compared, and the effect of crystallographic texture on corrosion resistance of the alloy was deeply described. The results showed that at the early stage of immersion, a layer of compact and flat film formed easily on surfaces of both oriented samples. With prolonged immersion time, the degradation of formed corrosive films started and their severity was quite sensitive to the composed crystallographic planes of sample surfaces. For the surface containing highly concentrated orientation of {10–10} and {11–20} prism planes, the degradation of formed corrosive film was quite slight and only occurred at some particular sites even after immersion for 48 h. Thus, the film could keep good corrosive protection to the underneath substrate. However, for the surface containing {0002} basal planes, {10–10} and {11–20} prism planes, the degradation of corrosive production film occurred widely, resulting in further decrease in the corrosion resistance of immersed samples.